#TITLE_ALTERNATIVE# - RIZAL ABDA (NIM : 10208077); Pembimbing : Dr. Eng.Bagus Endar B. Nurhandoko, MOCHAMMAD
Generally, ini geophysics exploration , earth subsurface considered as the isotropic medium which has no variation in lateral velocity. In fact, earth subsurface has weak to strong lateral velocity variation ( anisotropic ) and commonly caused pitfalls ini seismic data processing. Pitfalls ini seismic data processing could be major problem in seismic data interpretation which leads to failure in interpretation. This study observed the seismic wave propagation in anisotropic media, matrix of elasticities, and the influences of thomsen paramter toward reflection of seismic waves. The difference in characteristic between isotropi and anisotropic medium comes in wavefront and the values of elasticity parameters. Giving the appropiate values of anisotropic paramters could increase the quality / resolution in seismic data. Hence, in this study there will be shown the effect of various anisotropic paramters values toward depth migration process using kirchoff integral method. Model used for migration comes from reflection result between incident wave to the subsurface layers. And then , the traveltime generated by previous step would be used as input in depth migration. The effect of anisotropic medium shown in migration result was characterized by their distribution in subsurface layers.